The Role of Civil Society in Preventing Children from Smoking at Malaysia - Kertati, Indra; Aeni, Candra; Panggabean, Christina Innocenti Innocenti Tumiar; Abdullah, Dessy; Amelia, Rinita (Universitas Nurul Jadid, 2024)
Smoking among teenagers has become a global issue that concerns both society and governments. Global data shows that, on average, more than 25 percent of children in each country smoke. In developing countries, this number far exceeds that of developed countries. The latest trend among children under 18 years old is shifting from conventional to electronic cigarettes. The dangers of both are no longer being considered as the trend of electronic cigarettes is on the rise. Statistics from the Central Statistics Agency (BPS) indicate that the majority of children who smoke come from smoking families. Children exposed to adult smokers will experience health problems in addition to participating in smoking. The Indonesian School Kuala Lumpur (SIKL) is concerned about children picking up the habit of smoking; therefore, they hope to raise awareness among children to protect them from the dangers of smoking, both conventional and electronic. The aim of this Community Service is to increase awareness among students at SIKL to understand the dangers of smoking. The method used includes lectures and interactive discussions to stimulate children to think positively. The results of the community service show that children were enthusiastic and willing to remind each other if they encounter peers or friends smoking, including reminding their extended family members who smoke. Children were also enthusiastic about avoiding smokers to prevent themselves from becoming passive smokers. Therefore, it can be concluded that raising awareness about the dangers of smoking and the involvement of civil society in preventing smoking among children are crucial in controlling the spread of smoking-related diseases